Alendronate induced femur fracture complicated with secondary hyperparathyroidism. - Jain, SK; Roy, SP; Nagi, ON (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):501-506 The abstract of this article is available on the PubMed website